Pesticide exposure and inducible antipredator responses in the zooplankton grazer, Daphnia magna Straus - Pestana, JLT
Risk assessment of toxic substances under ecologically-relevant scenarios which include the presence of natural stressors is essential to understand their indirect toxic effects and to improve prediction of the impacts of contamination on community structure and ecosystem function. Here, we study the effects of the pesticide imidacloprid on the responses of Daphnia magna to a combination of predator-release kairomones from trout and alarm cues from conspecifics, simulating different levels of perceived predation risk. The joint effects of simultaneous exposure to both types of stressors were assessed both by traditional analysis of variance and by employing conceptual models for the evaluation of contaminant mixture exposures. Results demonstrated that pesticide exposure can significantly increase the costs of inducible antipredator defences and impair life-history responses of daphnids to fish predation pressure. Since trait-mediated effects are well-known to play a key role in population dynamics, the combined direct and indirect effects of sub-lethal concentrations of pesticides could induce maladaptive responses in zooplankton populations in the field, reducing their longterm viability. (C) 2009 Elsevier Ltd. All rights reserved.